2020
DOI: 10.3390/en13051022
|View full text |Cite
|
Sign up to set email alerts
|

Zeotropic Mixture Selection for an Organic Rankine Cycle Using a Single Screw Expander

Abstract: The organic Rankine cycle (ORC) is a popular and promising technology that has been widely studied and adopted in renewable and sustainable energy utilization and low-grade waste heat recovery. The use of zeotropic mixtures in ORC has been attracting more and more attention because of the possibility to match the temperature profile of the heat source by non-isothermal phase change, which reduces the irreversibility in the evaporator and the condenser. The selection of working fluid and expander is strongly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In this work, R1234yf was selected as a component of the zeotropic mixture, and R236ea was selected as the other component. The point on the saturated vapor line with the maximum specific entropy is called the turning point, as shown in Figure 2 [34,35]. Figure 3 shows the parameters of the critical point, as well as the turning point, of R1234yf/R236ea mixtures of various mole fractions calculated using REFPROP 9.1.…”
Section: System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, R1234yf was selected as a component of the zeotropic mixture, and R236ea was selected as the other component. The point on the saturated vapor line with the maximum specific entropy is called the turning point, as shown in Figure 2 [34,35]. Figure 3 shows the parameters of the critical point, as well as the turning point, of R1234yf/R236ea mixtures of various mole fractions calculated using REFPROP 9.1.…”
Section: System Descriptionmentioning
confidence: 99%
“…Cycle layout design is affected by the thermodynamic properties of working fluids and heat source temperatures. Zhang et al [34,35] pointed out that the turning-point temperature was the limit of a subcritical ORC with a conventional expander. Wang et al [36] concluded that, when the working fluid temperature at the turbine inlet was greater than its turning point, a superheated or supercritical ORC should be employed to avoid liquid forming during expansion in the turbine.…”
Section: Introductionmentioning
confidence: 99%